Tuck Everlasting - Literature Kit Gr. 5-6. - Renaud, Lisa (Literature Kits Grades 5-6., 2016)
In this State Standards-aligned Literature Kit™, we divide Natalie Babbitt's classic TUCK EVERLASTING by chapters, and feature reading comprehension and vocabulary questions.